(untitled) (Ozone Therapy Global Journal, 2024)
Cardiovascular diseases continue to be the leading cause of death in most Western countries. According to the World Health Organization, ischemic heart disease generally refers to conditions involving the narrowing or blockage of blood vessels, caused by damage to the heart or blood vessels due to atherosclerosis. This case presents a hypertensive ischemic heart disease with a background of uncontrolled Diabetes Mellitus 2, dyslipidemia, and obesity. Because ozone therapy can activate the antioxidant system, improve blood circulation, and enhance oxygen delivery to tissues, the patient was treated from the onset with Ozonated Saline Solution (SSO3) via micro-bubbling for 5 consecutive days, aiming to stabilize the patient as quickly as possible and establish the therapeutic efficacy of ozone combined with baseline antithrombotic and antihypertensive therapy. The patient presented with chest pain, severe fronto-occipital headache, and significant dyspnea. The patient was admitted to intensive care where, through Angio-CT and echocardiography, the following were diagnosed: ischemic and hypertensive heart disease, concentric hypertrophy of the left ventricle, mitroaortic sclerosis and calcification, and hypokinesia of the distal third of the septum and the apex. The patient responded favorably to the combination therapy, being transferred to the general ward after 48 hours with oxygen support (nasal cannula) maintaining normal saturation. Treatment was continued there for 15 days. Discharge was granted after 15 days of hospitalization under strict outpatient treatment and follow-up. It was established that Ozonated Saline Solution via micro-bubbling as a complement to baseline therapy was safe and effective in this patient.